Analysis of Student Learning Difficulties in Solving Calculus II Course Case Studies - Sulistyaningtyas, Annisa Dwi; Wantika, Restu Ria (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
Calculus II is a compulsory course in the Mathematics Education Study Programme of PGRI Adi Buana University Surabaya which is programmed by third semester students. This course learns about the basic concepts of integrals and their applications, so students are required to be able to understand and analyse problems appropriately. This study aims to determine the difficulties experienced by students in solving Calculus II problems as well as to find out the causes. The research subjects were five students of Mathematics Education of Universitas PGRI Adi Buana Surabaya in the academic year 2022/2023. This research uses a qualitative approach using test and interview methods. The results obtained from this study are in the form of types of student difficulties in solving problems, namely difficulty in determining the final result, difficulty in understanding the concept of function decomposition, difficulty in applying concepts to problems, difficulty in calculating, difficulty in starting the first step of the calculation. Furthermore, for the causes of these difficulties, including, lack of accuracy in understanding the problems given, lack of mastery of concepts, errors in the calculation process, and lack of understanding of the concept of initial identification of integral forms.